Social‐ecological reflexivity of extractive industry governance? The case of the Extractive Industries Transparency Initiative in Indonesia - Yanuardi, Yanuardi; Vijge, Marjanneke J.; Biermann, Frank (John Wiley and Sons Ltd, 2022)
The Extractive Industries Transparency Initiative (EITI) sets standards to improve the governance of extractive industries and thereby stimulate sustainable development. Member countries implement this standard through a multi-stakeholder group (MSG) which facilitates deliberation between government, civil society and business representatives. This deliberation could enable what we call ‘social-ecological reflexivity’: the ability to reconfigure oneself in response to critical reflection on one's performance in governing not only the economic, but also the social and environmental dimensions of sustainable development. Such reflexivity is crucial for countries to not only comply with the EITI standard, but also improve governance quality to address the social and environmental impacts from extractive industries. Drawing on a fully operationalised conceptual framework, we analyse social-ecological reflexivity in the implementation of the EITI in Indonesia, a country that is heavily impacted by extractive industries. We draw on content analysis of the MSG meeting minutes and EITI-Indonesia reports between 2012 and 2019. We show that the EITI-Indonesia has not (yet) generated deep social-ecological reflexivity. First, there is limited recognition and rethinking of extractive industry governance and no real response in the form of governance reforms. Second, there are even signs of what we call ‘anti-reflexivity’, whereby members of the multi-stakeholder group ignore and resist public debates around the negative impacts from extractive industries. In analysing the different components and degrees of reflexivity around the EITI-Indonesia, the article provides vital insights into the (study of) conditions under which global norms such as the EITI find meaning in and affect specific contexts.
Keywords: Extractive Industries Transparency Initiative; Indonesia; reflexive governance; reflexivity; sustainable development